PELATIHAN IMPLEMENTASI INTERNATIONAL SAFETY MANAGEMENT CODE UNTUK CREW KAPAL PT. SPIL: TRAINING ON THE IMPLEMENTATION OF THE INTERNATIONAL SAFETY MANAGEMENT CODE FOR PT. SPIL SHIP CREW - Agus Garjito; Della Fadila; Tri Gunawan Prasetyo; Adrian Dyca Zandyca; Kuncowati; Daryanto (Universitas Hang Tuah Surabaya, 2026)
The implementation of the International Safety Management (ISM) Code is a crucial component in improving maritime safety and preventing occupational accidents on ships. However, in practice, there are still cases where the crew's understanding of safety procedures, the implementation of the Safety Management System (SMS), and the work safety culture in the ship's operational environment are not yet optimal. This community service activity aims to improve the understanding and competence of PT SPIL's ship crew in implementing the ISM Code through practice-based training and participatory discussions. The implementation method used a hands-on training approach, material delivery, safety procedure simulations, evaluation of the Safety Management System (SMS) implementation, and evaluative discussions. The activity was conducted with PT SPIL's ship crew, consisting of officers and ship ratings. The results showed an increase in crew understanding of company safety policies, emergency procedures, reporting non-conformities, the use of safety equipment, and the implementation of a safety culture on board. Furthermore, the practice-based training was proven to improve crew preparedness in dealing with emergencies and support more effective implementation of the ISM Code. This activity positively contributed to improving safety culture and compliance with international maritime safety regulations